DIETA ESTACIONAL DEL COYOTE CANIS LATRANS DURANTE EL PERIODO 1996-1997 EN EL DESIERTO DE VIZCAÍNO, BAJA CALIFORNIA SUR, MÉXICO - Grajales Tam, Karina M.; Rodríguez Estrella, Ricardo; Cancino Hernández, Jorge (Instituto de Ecología, A.C., 2003)
We studied the diet of the coyote (Canis latrans) in the Vizcaino desert, Baja California Sur, México. The studied was carried out in the summer and winter seasons of 1996 and 1997, respectively. We analized 302 feces and determined 8963 prey items, for 64 animal taxa and 10 of plants. Arthropods were the most frequent prey, representing 95% of identified items in the winter. Prey weight 0 to 20 g was the most consumed prey size category although ingested biomass was greater from the 1280 to 2560 g prey category. The B values indicate that the coyote in the Vizcaino desert showed a trend to be a relatively specialist predator on arthropods.